2008
DOI: 10.1007/s11051-008-9433-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and controlled transformation of nitrate in water and brine by stabilized iron nanoparticles

Abstract: Highly reactive zero-valent iron (ZVI) nanoparticles stabilized with carboxymethyl cellulose (CMC) were tested for reduction of nitrate in fresh water and brine. Batch kinetic tests showed that the pseudo first-order rate constant (k obs ) with the stabilized nanoparticles was five times greater than that for non-stabilized counterparts. The stabilizer not only increased the specific surface area of the nanoparticles, but also increased the reactive particle surface. The allocation between the two reduction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The reaction kinetics of D-NZVI and D-Ni-NZVI followed a pseudo-first-order reaction, with a k obs value of 1.06 × 10 −1 min −1 (R 2 = 98.6%) for D-NZVI and 5.04 × 10 −1 min −1 (R 2 = 96.7%) for DNi-NZVI. It should be noted that previous studies have reported that the chemical reduction of nitrate by ZVI or NZVI powder generally follows pseudo-first-order reaction kinetics [6,8,38,40,41]. However, the reaction rates in our study could not be described by pseudo-first-order reaction kinetics, except for D-NZVI and D-Ni-NZVI; the reaction rate was 1.37-order and 1.72-order for DS-NZVI and DS-Ni-NZVI, respectively, with k obs values of 1.99 × 10 −2 min −1 (R 2 = 92.2%) and 1.89 × 10 −2 min −1 (R 2 = 99.1%).…”
Section: Nitrate Reduction By Nzvi and Effects Of Aggregation And Catmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction kinetics of D-NZVI and D-Ni-NZVI followed a pseudo-first-order reaction, with a k obs value of 1.06 × 10 −1 min −1 (R 2 = 98.6%) for D-NZVI and 5.04 × 10 −1 min −1 (R 2 = 96.7%) for DNi-NZVI. It should be noted that previous studies have reported that the chemical reduction of nitrate by ZVI or NZVI powder generally follows pseudo-first-order reaction kinetics [6,8,38,40,41]. However, the reaction rates in our study could not be described by pseudo-first-order reaction kinetics, except for D-NZVI and D-Ni-NZVI; the reaction rate was 1.37-order and 1.72-order for DS-NZVI and DS-Ni-NZVI, respectively, with k obs values of 1.99 × 10 −2 min −1 (R 2 = 92.2%) and 1.89 × 10 −2 min −1 (R 2 = 99.1%).…”
Section: Nitrate Reduction By Nzvi and Effects Of Aggregation And Catmentioning
confidence: 99%
“…To date, NZVI has been applied in many environmental remediation fields, including the adsorption of heavy metals and metalloids [2][3][4][5], the reduction of inorganic contaminants [6][7][8], and the dehalogenation of organic contaminants [9][10][11][12][13][14]. In particular, studies focusing on halogenated compound reduction have highlighted the outstanding reduction capabilities of NZVI [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Hwang et al [23] claimed that NaCl adsorption on the surface of the nZVI inhibited the rate of iron oxidation. Similarly, Xiong et al [18] claimed that the presence of 6% NaCl (w/w) decreased the observed reaction rate constant (K obs ) by 30% compared to the rate in fresh water (0.30 min −1 compared to 0.21 min −1 ), due to "double-layer compression effects", which led to increased agglomeration of the nZVI particles.…”
mentioning
confidence: 95%
“…Apparently, only one study [16] concluded that nitrate was reduced predominantly to N 2(g) as the end product. All other studies reported that between 85% and 90% of the nitrate was reduced to TAN and only the rest of the nitrate (i.e., less than 15%) was reduced to N 2(g) (e.g., [17][18][19]). Other studies (e.g., [13,14]) reported that almost 100% of the NO 3 − was reduced to TAN.…”
mentioning
confidence: 99%
“…Nitrate removal by nZVI generally occurs via reduction to ammonium (Eq. (1)) at very high rate (50 ppm nitrate could be reduced by 1.43 g/L nZVI within 1 h, as modeled by pseudo-first-order reaction kinetics), even at high pH (9)(10) [19][20][21]. Although there are several studies on the use of nZVI for cleanup of Pb 2+ [22][23][24] or nitrate contamination [18,19] individually, little attention has been paid to the treatment of groundwater with different levels of Pb 2+ and nitrate, even though some researchers recommend that studies need to be done in the systems similar to the real environment [25,26].…”
Section: Introductionmentioning
confidence: 99%